FROM CONCEPTUAL DESIGN TO IMPLEMENTATION STAGE OF INTEGRATIVE GIS GEOSCIENCE SPATIAL DATABASES USING THE GEOSEA DATA MODEL - , Lucas Donny Setijadji ([Yogyakarta] : Ikatan Ahli Geologi Indonesia, 2008)
Several GIS-based geoscience data models are available, such as the the North America Digital Geologic Map Data Model (NADM), the eXploration and Mining Markup Language (XMML), the Commission for the Management and Application of Geoscience Information (CGI) of the International Union of Geological Sciences (IUGS), and the ESRI Geology Data Model (EGDM). However, integration of different data models is still challenging. This study pursues such an integrative model by integrating existing data models and naming it the GeoSEA data model which is expected to support different geoscience projects in geological mapping, earth resources, and geo-hazards at the SE Asia continental margin setting. This model uses the conceptual model of the NADM-C1.0 as the base for developing extended data models for earth resources and geo-hazards. The structural organization of data model is organized into packages, supergroups, groups, and classes. Packages are containers used to organize UML elements into specific projects. This is merely an organization issue as UML elements of different packages can actually be shared with or moved into other packages. Within each package, UML elements are organized into supergroups, groups, and individual classes. In current model, there are three packages created, i.e. the geologic map, earth resource, and geo-hazard models. The geologic map package becomes a center of modeling as most object classes are modeled here. The earth resource and geo-hazard packages are used to organized UML elements which are very case-specific for respective purposes. Implementation of conceptual model has been started from Yogyakarta and surrounding regions, in which various geoscience research projects are evolving here, such as the study on still very active Merapi volcano, the devastated earthquake 27 May 2006, and the porphyry gold-copper deposit prospect at Selogiri district. Beberapa database model kebumian yang berbasis GIS sudah tersedia, seperti North America Digital Geologic Map Data Model (NADM), eXploration and Mining Markup Language (XMML), Commission for the Management and Application of Geoscience Information (CGI) dari International Union of Geological Sciences (IUGS), dan ESRI Geology Data Model (EGDM). Namun demikian, integrasi dari berbagai jenis data model tersebut masih menjadi tantangan. Studi ini mencari proses integrasi tersebut untuk menghasilkan suatu data model yang terintegrasi dan menamakannya GeoSEA data model yang diharapkan dapat mendukung berbagai proyek cabang-cabang ilmu kebumian yang berbeda seperti untuk pemetaan geologi, sumber daya geologi dan bencana kebumian di kawasan Asia Tenggara. Data model ini menggunakan basis model konseptual dari NADM-C1.0 yang kemudian dikembangkan untuk bidang-bidang lain seperti sumber daya geologi dan bencana geologi. Organisasi struktural data model ditata dalam beberapa package, supergroup, group, dan class. Package adalah wadah untuk mengorganisir element-element UML ke dalam thema-thema yang spesifik. Ini semata-mata adalah masalah pengorganisasian karena elemen-elemen UML dari berbagai package sesungguhnya dapat di-share atau dipindahkan ke dalam package lain. Di dalam setiap package, elemen-elemen UML diorganisasikan ke dalam supergroup, group, dan class. Dalam model yang saat ini dibuat, terdapat tiga package yang dibuat, yaitu package untuk peta geologi, sumber daya geologi, dan bencana geologi. Package peta geologi menjadi pusat pemodelan karena sebagian besar object class dimodelkan di sini. Package untuk sumber daya geologi dan bencana geologi dipakai untuk mengorganisasikan elemen UML yang sangat spesifik di bidangnya. Implementasi dari data model ini telah dimulai dari daerah Yogyakarta dan sekitarnya, di mana banyak program riset di berbagai bidang ilmu kebumian saat ini sedang berlangsung, seperti studi tentang gunung Merapi yang masih sangat aktif, gempa bumi Yogyakarta 27 Mei 2006, dan deposit emas-tembaga porpiri di Selogiri.